Gestão educacional: construindo parâmetros na prática participativa da gestão escolar da E. E. E. F. José Vieira - Silva, Adeilton Santos da (2018)
The present theme is configured in the aspect of the advance of policies educational and their connections with the theme of participative and democratic management. Therefore, our concern is about analyzing the Parameters of School Management and how they relate and can contribute to a democratic and participatory management in the school management of the E E. E. F. José Vieira. Our specific objectives are to: Understand how the relations in the Educational Management of E.E.E.E. José Vieira; Recognize the elements of Education; Identify the principles of School Management in line with participatory practice; And, finally, specify the role of the School Manager, the profile and their competencies. The methodology consists of qualitative and field research. To do so, we used the experiences of the internships and questionnaire applied with the manager and part of the school community. The results confirm our hypothesis that the Management made with managers who develop parameters for a participatory practice in School Management is in line with what the legal frameworks and the co-participants indicate that it is part of a democratic management.